Partnering dance and education : intelligent moves for changing times - Hanna, Judith Lynne (Human Kinetics, 1999)
n Partnering Dance and Education, Dr. Judith Lynne Hanna presents a compelling argument for making dance central to every student's education. She examines current trends and issues in education to show how dance can be successfully justified and taught in today's changing educational environment.